Modified tibial plateau levelling osteotomy to treat lateral patellar luxation and cranial cruciate ligament deficiency in a dog - Curuci, Eloy H. P. [UNESP] (2021)
The use of modified tibial plateau leveling osteotomy adapted for correction of the lateral patellar dislocation was effective, allowing simultaneous treatment of lateral patellar luxation and cranial cruciate ligament deficiency.